FORTIFIED FAR RIGHT? scrutinizing the threat. - Pethő-Kiss, Katalin ([S.l.] : ROUTLEDGE, 2024)
Petho-Kiss and Gunaratna understand the nature of the threat posed by the far right because of their findings and they propose effective provisions and mechanisms for detecting and countering it. The book undertakes a consistent procession and empirical examination of available information to arrive at the recognition that in order to dissolve the complexity of the associated threat, we need to scrutinize the functioning of far-right threat groups. In-depth and consistent analysis on their mode of operation and mindset enables us to identify ways to detect and counter their malicious efforts and activities. The theoretical framework for the analysis lies upon the concept of wave theory. The main question that this book examines is whether far-right terrorism constitutes a new wave of global terrorism. One question emerges from this statement that requires further elaboration. Is far-right terrorism a novel wave of terrorism? If yes, how is it novel and what are the novelties or developments in it? This book is for scholars as well as practitioners in the counter-terrorism (CT) and the prevention/countering violent extremism (PCVE) field. Through specific case studies students studying CT and/or PCVE could gain insight into the operational functionalities of far-right threat groups. This may help them to get a more accurate understanding of the threat posed by these entities. Examining the recruitment, funding, communication practices, and modus operandi of worrisome threat actors equips us to design the most effective countermeasures and identify the hiatuses in applicable legislative regimes.
Keywords: Authoritarianism; Totalitarianism; POLITICAL SCIENCE / Political Freedom & Security / Terrorism; POLITICAL SCIENCE / Political Freedom & Security / International Security; POLITICAL SCIENCE / Political Freedom & Security / Intelligence